Longitudinal measurement of serum cartilage oligomeric matrix protein can detect the progression of cartilage degeneration in anterior cruciate ligament reconstruction patients - Yohei Nishida; Yusuke Hashimoto; Kumi Orita; Kazuya Nishino; Takuya Kinoshita; Ken Iida; Hiroaki Nakamura (Elsevier, 2024)
Background/objective: Cartilage oligomeric matrix protein (COMP) has utility as a diagnostic marker for osteoarthritis (OA). Our previous study revealed that the serum COMP level can be used to detect early cartilage change in non-OA patients with anterior cruciate ligament (ACL)-deficiency. However, there are still no studies on detecting the progression of cartilage degeneration in early OA. The aim of present study was to investigate whether serum COMP can detect the progression of cartilage degeneration after ACL reconstruction in non-OA patients. Methods: Patients without cartilage degeneration of early OA at ACL reconstruction and whose serum COMP levels could be measured were included in the study. Cartilage degeneration of early OA were defined as International Cartilage Repair Society (ICRS) grade 1 to 4 in more than 2 compartments or ICRS grade 2 to 4 in 1 compartment. The patients were divided into two groups: those who had cartilage degeneration of early OA at second-look arthroscopy (cartilage degeneration progression group) and those who did not (non-progression group), and the serum COMP values between the two groups were compared. Results: Thirty-one patients were included. There were 8 cases (25.8 %) in progression group and 23 cases (74.2 %) in non-progression group. There were significant differences between the two groups regarding age and change in serum COMP level. In terms of the rate of change in COMP, an increase of more than 1.24-fold was the cut-off value for detecting the progression of cartilage degeneration. Conclusions: In this study, the increase in serum COMP levels was significantly greater in progressed cartilage degeneration group than non-progression group after ACL reconstruction. Longitudinal serum COMP measurement could detect the progression of cartilage degeneration. Level of evidence: Level Ⅲ, retrospective comparative study.